Total and Specific Immunoglobulin E and Their Relationship to Respiratory Symptoms in Quebec Children and Adolescents - Benoît Levesque; Jean-François Duchesne; Suzanne Gingras; Pierre Allard; Edgar Delvin; Jacinthe Aubin; Marc Rhainds; Pierre Lajoie; Pierre Ernst (Canadian Respiratory Journal)
BACKGROUND: Respiratory disease is a major cause of morbidity in young people. It is now recognized that atopy plays an important role in the development of chronic respiratory symptoms in children.